Application of hydroxyapatite-based nanoceramics in wastewater treatment: Synthesis, characterization, and optimization - Oladipo, Akeem Adeyemi; Gazi, Mustafa (Springer International Publishing, 2016)
In recent years, increasing environmental issues, particularly relating to biogenic and chemical pollution of water, have become a significant threat to both human health and the ecosystems. Many of these wastewaters contain a high level of contaminants which are undesirable because they create odor, bad taste, toxic effects aside the unpleasant aesthetic nature of the water. Hence, the removal of these toxic pollutants is necessary and, has attracted considerable efforts particularly via adsorption technology. Hydroxyapatite is among the most representative ceramic materials and considered promising for long-term containment of toxic pollutants due to its eco-friendly nature, good dispersibility, outstanding stability, and abundant modifiable surface functional groups. This chapter highlights the significance of sol–gel synthesis routes for producing hydroxyapatite-based nanoceramic for environmental applications. General summary of other synthesis methods and recent applications of hydroxyapatite-based nanoceramic as adsorbents and catalysts are reviewed. The wastewater parametric conditions and the synthesized hydroxyapatite-based materials covered herein is expected to inspire and stimulate further applications of nanoceramic-based materials in the environmental science. © Springer International Publishing AG 2017.
Keywords: Ceramic materials; Environmental protection; Health risks; Hydroxyapatite; Nanocatalysts; Sols; Toxic materials; Water pollution; Adsorption technology; Chemical pollution; Dispersibilities; Environmental applications; Environmental issues; Environmental science; Parametric conditions; Surface functional groups; Wastewater treatment